Partisipasi Kelompok Masyarakat Dalam Pelestarian Hutan Mangrove Di Desa Margasari Kecamatan Labuhan Maringgai Kabupaten Lampung Timur - Askasifi Eka Cesario; Slamet Budi Yuwono; Rommy Qurniati (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
The damage of mangrove forests as a green belt in the east coast of Lampung was very concerning. This research was conducted on April 2014 in Margasari village Labuan Maringgai District of East Lampung regency. The participation of villagers community that included Margajaya Utama community, Margajaya Satu community, Environmental Education (PLH), Shrimp Paste (terasi) processing group, Farmers group, Fishermen group, and fish processing group give impacts of mangrove conservation. The purpose of this research were to determine the type of institutional participatory and the level of participation society groups of mangrove forests conservation. The method used descriptive quantitative by administering a score in each category answers and descriptive qualitative to present the type of participatory institutional which has definition as participation of each institution member to develop a better institution. Result of the research found that the level of participation of the community in mangrove forests conservation had been very good and Margajaya community was the best one which has mobilisasi swakarsa as type of participatory institutional. Based on the results of the research, it can be concluded that the type of participatory institutional consists of passive participation in the group of farmers, fish processing group, shrimp paste processing (terasi) group and fishermen groups, participation in consultative is community of environmental education and mobilization swakarsa of participation, consists the group of margajaya. The level of participation of community groups in the preservation of mangrove forests on the highest category is 73.68% that is supported by the margajaya group and community of environmental education, then medium category is 19.74% that included farmers group, fish processing group, and fishermen group, then 6.58% of low category is farmers group and shrimp paste (terasi) processing group. Keywords: Mangrove forest, community group society, conservation